WTO LEGAL REFORM: THE NEED FOR REVISITING THE TREATMENT ACCORDED TO CHINA AS A NON-MARKET ECONOMY IN TRADE REMEDIES - Ramirez Martinez, Luis C. (Tufts Archival Research Center, 2019)
Submitted in partial fulfillment of the degree Masters of Law in International Law at the Fletcher School of Law and Diplomacy. The case of the non-market economy treatment to People’s Republic of China, (China), at the World Trade Organization, (WTO), might be the typical case where reality (economic) outdoes theory (legal) or, perhaps, expectations. By 2001, when the WTO let China in, its Protocol of Accession, PoA, included provisions regarding the features of its economic model. Today China and other members fiercely fight over the validity of those, now allegedly, expired rules that suggested the commitment by which China would become a market driven economy within 15 years. This paper then discusses the conditions for a reform to the WTO’s trade remedies legal framework so as to solve that problem by means of a multilateral negotiation rather than these complex litigations. This is negotiation is suggested as the most appropriate, pragmatic, and long-lasting means to ensure the preservation and efficacy of the WTO trade remedies mechanism. Otherwise, increasingly complex bilateral litigations will harm its creditworthiness.